Effects of bio-organic fertilizer made from Chinese traditional herb residues on heavy metal passivation in Cd and Hg compound-contaminated soils - CHEN Fen; YU Gao; WU Hanqian; HOU Jianwei; ZHAO Chenggang (浙江大学学报. 农业与生命科学版, 2020)
This study aimed to understand the passivation effects and mechanisms of bio-organic fertilizer made from Chinese traditional herb residues (BOFCTHR) on heavy metals in farmland soils. The soils with three levels of Cd-contamination were collected from Longli County (high pollution), Wanshan District, Tongren City (medium pollution), and Danzhai County (low pollution) in Guizhou Province. A soil incubation experiment was conducted to study the effect of BOFCTHR on soil organic matter, pH, cation exchange capacity (CEC), the morphological transformation of Cd and Hg, immobilization efficiency (IE) and mobility index (MI) under the addition of 0 (CK), 1.5%, 3.0% and 6.0% BOFCTHR, respectively; and the correlation between the physiochemical properties of soils and the forms of heavy metals was analyzed. The results showed that the application of BOFCTHR increased significantly soil organic matter content, pH, and CEC in a dose-dependent manner. The application of BOFCTHR decreased exchangeable and carbonate-bound form contents of Cd and Hg, increased organic-bound and residual form contents of Cd and Hg; and the reduce amplitude of exchangeable and carbonate-bound form contents of Cd and Hg, and the increment amplitude of organic-bound and residual form contents of Cd and Hg followed the order: 6.0% BOFCTHR＞3.0% BOFCTHR＞1.5% BOFCTHR. The application of BOFCTHR decreased MI of Cd and Hg, and increased IE of Cd and Hg; and the reduce amplitude of MI of Cd and Hg, and the increment amplitude of IE of Cd and Hg followed the order: 6.0% BOFCTHR＞3.0% BOFCTHR＞1.5% BOFCTHR. The correlation analysis showed that soil organic matter content, pH, and CEC were significant negative correlation with exchangeable form content of Cd and Hg (P＜0.05), and significant or extremely significant positive correlation with organic-bound form content of Cd (P＜0.05 or P＜0.01); soil organic matter content and CEC were significant positive correlation with organic-bound form content of Hg (P＜0.05). It is concluded that BOFCTHR may affect the passivation effect of heavy metals in the soil by changing the physiochemical properties.